Investigation Into the Effect of Joint Clearance on the Dynamics of a Biomechanical Energy Harvesting System - Ludwin Molina Arias; Marek Iwaniec; Joanna Iwaniec (IEEE Access, 2023)
The existing clearance in the mechanical joints plays a crucial role in the assembly of mechanical systems, allowing the mobility of its components. However, few studies have explored models that consider joint clearance in the case of electromechanical energy harvesting systems. This paper examines the effect of existing clearance in an electromagnetic energy harvester attached to the human lower limb. The dynamic response of the system and an estimate of its generated power are obtained by developing a lumped model, in which clearance is included by adding a dead band and assigning a stiffness coefficient during contact between elements. The natural motion of the lower limb is the input to the formulated model, which takes into account the nonlinear interaction of the electromagnetic device and the power conditioning circuit. Central composite design is used to study the influence of two selected factors on the dynamics of the system; joint clearance size and contact stiffness. The results suggest that the presence of clearance between the clamping mechanism and the human body positively affects the performance of the analyzed electromagnetic energy harvesting system. It was revealed that an increase of around 27% of output power could be intentionally achieved by adding larger clearance sizes.